Antimicrobial Effect of the Crude Phenolic, Alkaloid and Terpenoid Compounds Extracts of Myrtus Communis L. against Human Gram-Negative Pathogenic Bacteria - Ali Hussein Al-Marzoqi (Journal of Global Pharma Technology, 2017)
Objective: To reveal the effect of the crude phenol, alkaloid and torpedoed compounds extracts of Mitres Communes L. on some Human gram-negative Pathogenic Bacteria. Methods Antibacterial activities of the crude Phenol, Alkaloid and Torpedoed of medicinal plant were determined in vitro by agar well diffusion-method against some human pathogenic bacteria. Results obtained results showed that active compounds of Mitres Communes L. had wide spectrum antibacterial activity against gram- gram-negative bacteria Conclusion This study demonstrates that we can conclude that the effect of active compounds in same plant has different effect on different pathogenic organisms in different concentrations.Keywords: Antimicrobial, Myrtus Communis, L Pathogenic Bacteria, Gram-negative Bacteria.